Reverendo Jeronimo Gueiros: Notas Póstumas de Recortes Jornalísticos (1953) - Silva, Drance Elias da; Souza, José Roberto de (Anais dos Simpósios da ABHR, 2016)
Reverendo Jeronimo Gueiros: Notas Póstumas de Recortes Jornalísticos (1953)